2009
DOI: 10.21608/jappmu.2009.119192
|View full text |Cite
|
Sign up to set email alerts
|

Non-Genetic Factors Affecting Somatic Cell Count, Milk Urea Content, Test-Day Milk Yield and Milk Protein Percent in Dairy Cattle of the Czech Republic Using Individual Test-Day Records

Abstract: This study had two aims. Firstly, to determine the associations of month of recording (MOR) and days in milk (DIM) with somatic cell count (SCC), milk urea concentration (MU) and milk production traits (i.e. test-day milk yield, TDM; milk protein percentage, PP and milk protein yield, PY). Secondly, to evaluate the associations among SCC, MU and milk production traits by analyzing individual monthly test-day records for dairy cows raised in the Czech part of the Czech Republic. A total number of 33,881 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…Almost similar finding was observed by Kennedy et al, (1982) and Schutz et al, (1990) who reported SCC score high in beginning stages of lactation and contrary report by Kataria and Kataria (2006), Kamboz et al, (2007) and Kumaresen (2013) SCC was observed significant high in late lactation than early and mid lactation stages. Above results are with close agreement with result of Oudah (2009) who reported slightly increased in first four months than declined gradually end of lactation. Ouedraogo et al, (2008) found that the low milk yield was associated to higher somatic cell count.…”
Section: Mean ± S E Values Of Milk Yield Milk Composition Scc and Bcs During Complete Lactation In Hf Crossbred Cows In Tablesupporting
confidence: 92%
“…Almost similar finding was observed by Kennedy et al, (1982) and Schutz et al, (1990) who reported SCC score high in beginning stages of lactation and contrary report by Kataria and Kataria (2006), Kamboz et al, (2007) and Kumaresen (2013) SCC was observed significant high in late lactation than early and mid lactation stages. Above results are with close agreement with result of Oudah (2009) who reported slightly increased in first four months than declined gradually end of lactation. Ouedraogo et al, (2008) found that the low milk yield was associated to higher somatic cell count.…”
Section: Mean ± S E Values Of Milk Yield Milk Composition Scc and Bcs During Complete Lactation In Hf Crossbred Cows In Tablesupporting
confidence: 92%
“…This device is a combination instrument consisting of the MilcoScan TM FT+ and the Fossomatic TM FC. To convert MU into MUN, the following conversion formula was used: MUN (mg/dl) = MU (mg/dl) × 0.4667 (Oudah EZM, 2009). The principle of analyzing of raw milk samples is based on the methodology by mid -infrared spectrometry method (ISO 9622 /2013).…”
Section: Methodsmentioning
confidence: 99%
“…Milk samples were analysed for: the total protein content, fat, lactose, and urea concentration by spectrophotometric tests in the near-infrared region using MilkoScan FT+ and BENTLEY FTS in the Central Analytical Laboratory for milk with accreditation under registration number 096/5878/2015/2. The analysed content of urea in milk (MU) was converted to urea nitrogen in milk (MUN) according to O u d a h [26].…”
Section: Analysis Of Production Parametersmentioning
confidence: 99%